(untitled) (Al-Qamar, 2023)
The word blessing has been used many times in Shariah’s and lexical. Which has been interpreted with permanence and multiplicity. In the Sharia’s sense, it is applied to the goodness placed by Allah in anything which is in the form of multiplicity and continuity or is devoid of them. Allah Almighty has the power to keep this goodness in certain people, things, times and places while depriving some of them. That is why obtaining blessings from thing needs a Shari’s evidence. Where there is evidence, the blessing will be valid and where there is no Shari’s text, the blessing will not be valid. Allah has blessed some objects, persons and places and times with grace, grace and position.